Danggui Shaoyao San and disassembled prescription: neuroprotective effects via AMPK/mTOR-mediated autophagy in mice - Xiaoqing Cheng; Yuqiong Dai; Baoling Shang; Shuting Zhang; Liting Lin; Qingguang Wu; Ruoting Zhan; Shengqing Li; Sijun Liu (BMC, 2024)
Abstract Background Danggui Shaoyao San (DSS), a frequently prescribed Chinese medicine formula, has demonstrated clinical efficacy in the treatment of Alzheimer's disease (AD). This study aims to explore the differences in therapeutic effects of DSS and its disassembled prescriptions, Suangan (SG) and Xingan (XG), in treating Alzheimer's Disease and the mechanism of DSS recovering autophagy in AD. Methods A network pharmacology strategy was employed to delineate the bioactive constituents, associated targets, and regulatory mechanisms of DSS in AD, encompassing in silico target forecasting, the generation and scrutiny of PPI networks, alongside GO and KEGG-based pathway elucidation. An AD mouse model, induced by intracerebroventricular injection of Aβ1-42, was used to evaluate the therapeutic effects of DSS and its disassembled prescriptions on AD. Cognitive function was evaluated using the Morris water maze. Expression levels of inflammatory cytokines were quantified via RT-qPCR and ELISA. Western blotting was used to detect the expression of proteins related to AD pathological markers and the AMPK/mTOR signaling pathway. Results 50 active compounds and 718 HUB genes were screened from relevant databases and literature. KEGG and GO analyses indicated that DSS's potential mechanisms against AD involved the AMPK/mTOR signaling pathway and mitophagy. In vivo animal model, the results demonstrated that DSS, SG, and XG treatments improved cognitive function and ameliorated neuroinflammation in mice. Additionally, they alleviated the pathological changes of neuronal cells. These treatments also increased the protein level of PSD-95, and decreased levels of APP and p-Tau. Among them, DSS exhibited the best efficacy. Furthermore, DSS, SG, and XG upregulated the expression of LC3, Beclin1, and p-AMPK, while decreasing the expression of P62 and p-mTOR. Conclusions DSS, SG, and XG were found to ameliorate AD-related pathological symptoms in Aβ1−42-injected mice, likely through the AMPK/mTOR autophagy signaling pathway.